2021
DOI: 10.3389/fmicb.2021.698588
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium lepromatosis as a Second Agent of Hansen’s Disease

Abstract: Mycobacterium lepromatosis was identified as a new species and second causal agent of Hansen’s disease (HD, or leprosy) in 2008, 150years after the disease was first attributed to Mycobacterium leprae. M. lepromatosis has been implicated in a small number of HD cases, and clinical aspects of HD caused by M. lepromatosis are poorly characterized. HD is a recognized zoonosis through transmission of M. leprae from armadillos, but the role of M. lepromatosis as a zoonotic agent of HD is unknown. M. lepromatosis wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 56 publications
1
21
0
1
Order By: Relevance
“…Mycobacterium leprae was first described by Norwegian physician Dr Gerhard Henrik Armauer Hansen in 1874, while Mycobacterium lepromatosis was initially sequenced in 2008. 6 , 7 , 57 59 Both these bacteria have the functional capacity to cause leprosy, but are genetically dissimilar enough to be considered separate species. 6 , 59 Although leprosy was originally identified in the 19th century, historical records suggest that the pathogen has remained a global endemic disease for at least 3000 years.…”
Section: Leprosymentioning
confidence: 99%
See 1 more Smart Citation
“…Mycobacterium leprae was first described by Norwegian physician Dr Gerhard Henrik Armauer Hansen in 1874, while Mycobacterium lepromatosis was initially sequenced in 2008. 6 , 7 , 57 59 Both these bacteria have the functional capacity to cause leprosy, but are genetically dissimilar enough to be considered separate species. 6 , 59 Although leprosy was originally identified in the 19th century, historical records suggest that the pathogen has remained a global endemic disease for at least 3000 years.…”
Section: Leprosymentioning
confidence: 99%
“… 6 , 7 , 57 59 Both these bacteria have the functional capacity to cause leprosy, but are genetically dissimilar enough to be considered separate species. 6 , 59 Although leprosy was originally identified in the 19th century, historical records suggest that the pathogen has remained a global endemic disease for at least 3000 years. The pathogen rose to prominence in the 13th century as a consequence of urbanization and has since experienced a slow decline in prevalence.…”
Section: Leprosymentioning
confidence: 99%
“…After that, more and more patients were discovered. In a study conducted by Deps ( 5 ), more than 150 cases were reported worldwide, mainly from three endemic countries (Brazil, Philippines, and Myanmar) and three non-endemic countries (Mexico, Malaysia, and the USA). Notably, M. lepromatosis has also been reported in Colombia ( 6 , 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Leprosy is caused by an uncultivated pathogen, Mycobacterium leprae and Mycobacterium lepromatosis which primarily affect the skin, mucosal surface of the upper respiratory tract, the peripheral nerves, eyes, and internal organs (1,2). It has a long incubation period which can take as long as 20 years or more.…”
Section: Introductionmentioning
confidence: 99%